Implementing smart farming using internet technology and data analytics: a prototype of a rice farm - Eteng, Idongesit; Ugbe, Catherine; Oladimeji, Samuel (Eastern-European Journal of Enterprise Technologies, 2022)
Precision Agriculture which includes the implementation of smart farms is gradually becoming commonplace in our present world. The Internet of Things (IoT) and also Analytics techniques are useful tools for the actualization of smart farms as they allow for information dissemination to rural farmers and also serve as a platform for monitoring farm activities. When farm activities are properly monitored, food production is optimized. As the world’s population grows, there is a greater challenge of the availability of food. The combination of IoT and data analytics has not been fully explored for Smart farming especially in developing economies. This paper proposes a FarmSmart Application using an IoT-based mobile monitoring system that combines sensors, and data analytics to manage irrigation processes and broadcast Agricultural information to farmers. The FarmSmartApp was implemented on the IntelliJ IDE using C++ and MongoDB.Python and Excel were used for the data analytics. The effectiveness of the proposed system is examined on a real-world dataset harvested from the mounted sensors. Also an initial evaluation of the system is done by stakeholders. Simple Analysis of Variance of light, moisture and temperature led to the rejection of the null hypothesis of no significance difference in mean effect among the variables since fcalc is greater than fcrit justified by p value less than 0.05. On the system evaluation, 97 % of the examined stakeholders agreed that the system delivered on the agreed functionality .The system therefore has the capacity to provide farmers with useful Agricultural information to guide irrigation procedures and Agricultural decision making